Proof of concept for multirotor systems with vortex-generating modes for regenerative wind energy: a study based on numerical simulations and experimental data - F. Avila Correia Martins; A. van Zuijlen; A. van Zuijlen; C. Simão Ferreira (Wind Energy Science)
This study investigates the potential of regenerative wind farming using multirotor systems equipped with paired multirotor-sized wings, termed atmospheric boundary layer control (ABL-control) devices, positioned in the near-wake region of the multirotor. These ABL-control devices generate vortical flow structures that enhance vertical momentum flux from the flow above the wind farm into the wind farm flow, thereby accelerating the wake recovery process. This work presents numerical assessments of a single multirotor system equipped with various ABL-control configurations. The wind flow is modeled using steady-state Reynolds-averaged Navier–Stokes (RANS) computations, with the multirotor and ABL-control devices represented by three-dimensional actuator surface models based on momentum theory. Force coefficient data for the actuator surface models, as well as validation data for the numerical computations, were obtained from a scaled model at TU Delft's Open Jet Facility. The performance of the ABL-control devices was evaluated by analyzing the net momentum entrained from the flow above the wind farm and the total pressure and power available in the wake. The results indicate that, when the ABL-control strategy is employed, vertical momentum flux may become the dominant mechanism for wake recovery. In configurations with two or four ABL-control wings, the total wind power in the wake recovers to 95 % of the free-stream value at positions as early as x/D≈6<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="f1f50c65a676d34319b7e018d39c81d7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="wes-10-41-2025-ie00001.svg" width="42pt" height="14pt" src="wes-10-41-2025-ie00001.png"/></svg:svg> downstream of the multirotor system, representing a recovery rate that is approximately an order of magnitude faster than that observed in the baseline wake without ABL-control capabilities. It should be noted, however, that this study employs a simplified numerical setup to provide a proof of concept, and the current findings are not yet directly applicable to real-world scenarios.